Seismic anisotropy of Precambrian lithosphere: Insights from Rayleigh wave tomography of the eastern Superior Craton. Issue 5 (13th May 2017) - Petrescu, Laura; Darbyshire, Fiona; Bastow, Ian; Totten, Eoghan; Gilligan, Amy
Abstract: The thick, seismically fast lithospheric keels underlying continental cores (cratons) are thought to have formed in the Precambrian and resisted subsequent tectonic destruction. A consensus is emerging from a variety of disciplines that keels are vertically stratified, but the processes that led to their development remain uncertain. Eastern Canada is a natural laboratory to study Precambrian lithospheric formation and evolution. It comprises the largest Archean craton in the world, the Superior Craton, surrounded by multiple Proterozoic orogenic belts. To investigate its lithospheric structure, we construct a frequency‐dependent anisotropic seismic model of the region using Rayleigh waves from teleseismic earthquakes recorded at broadband seismic stations across eastern Canada. The joint interpretation of phase velocity heterogeneity and azimuthal anisotropy patterns reveals a seismically fast and anisotropically complex Superior Craton. The upper lithosphere records fossilized Archean tectonic deformation: anisotropic patterns align with the orientation of the main tectonic boundaries at periods ≤110 s. This implies that cratonic blocks were strong enough to sustain plate‐scale deformation during collision at 2.5 Ga. Cratonic lithosphere with fossil anisotropy partially extends beneath adjacent Proterozoic belts. At periods sensitive to the lower lithosphere, we detect fast, more homogenous, and weakly anisotropic material, documenting postassembly lithospheric growth, possibly in a slow or stagnant convection regime. A heterogeneous, anisotropic transitional zone may also be present at the base of the keel. The detection of multiple lithospheric fabrics at different periods with distinct tectonic origins supports growing evidence that cratonization processes may be episodic and are not exclusively an Archean phenomenon. Plain Language Summary: The roots of the oldest parts of the continents are unusually thick (∼250 km) and preserve structures dating back to the Earth's most ancient geological period, >2.5 billion years ago. The structure, formation, and preservation of these thick continental roots are still debated. Eastern Canada has a geological record stretching back over more than 3 billion years, providing an excellent opportunity to study the Earth's early history and the formation and evolution of continents. To investigate the deep structure beneath this region, we use earthquake energy recorded at seismic stations across eastern Canada to build an image of the continental interior. Our results show that the ancient continental root is made up of at least two layers, each with a different formation mechanism. The upper layer preserves the signature of continental deformation older than 2.5 billion years, whereas the lower layer properties suggest later downward growth of the root above a slow‐moving mantle. The results support the idea that the thick continental roots formed episodically and across multiple geological periods. Key Points: Fossil anisotropy preserved in the upper lithosphere suggests that cratonic blocks sustained plate‐scale collision in the Archean Lower cratonic lithosphere is weakly anisotropic, suggesting postassembly lithospheric growth in a slow convection regime Lowermost lithosphere is highly heterogeneous and anisotropic, and transition to underlying asthenosphere is complex